1981
DOI: 10.1111/j.1365-2621.1981.tb04489.x
|View full text |Cite
|
Sign up to set email alerts
|

Flavor Intensity as Related to the Creatine and Creatinine Content of Microwave and Conventionally Cooked Beef

Abstract: No relationship between sensory thresholds of panelists for creatine and their ability to detect differences in flavor intensity of beef prepared in a consumer type microwave oven (12OV; 55 0 watts) and a conventional oven was found. The flavor of beef cooked in an institutional type microwave oven (220V; 1050 watts) was rated more intense than conventionally cooked beef. However, the flavor of beef prepared in a consumer type microwave oven (115V; 500 watts) was evaluated as less intense than conventionally c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

1987
1987
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 17 publications
0
8
0
Order By: Relevance
“…Changes in moisture (%), creatine and creatinine content (mg/ 100 g muscle; fresh matter basis), and creatinine/creatine ratio of herring fillet during drying 1970). Snider and Baldwin (1981) also reported a significant (p < 0.05) positive correlation between flavor intensity and creatinine content of the cooked beef. On the other hand, addition of WSE of dried herring fillet to JNS significantly (p < 0.05) resulted in the highest enhancement of flavor characters such as thickness, mouthfulness and continuity of the JNS, whereas no significant (p > 0.05) changes were observed in saltiness and umami.…”
Section: Effect Of Ph Temperature and Drying Time On The Conversion mentioning
confidence: 89%
See 3 more Smart Citations
“…Changes in moisture (%), creatine and creatinine content (mg/ 100 g muscle; fresh matter basis), and creatinine/creatine ratio of herring fillet during drying 1970). Snider and Baldwin (1981) also reported a significant (p < 0.05) positive correlation between flavor intensity and creatinine content of the cooked beef. On the other hand, addition of WSE of dried herring fillet to JNS significantly (p < 0.05) resulted in the highest enhancement of flavor characters such as thickness, mouthfulness and continuity of the JNS, whereas no significant (p > 0.05) changes were observed in saltiness and umami.…”
Section: Effect Of Ph Temperature and Drying Time On The Conversion mentioning
confidence: 89%
“…Creatine and creatinine have been reported as taste active components in many foods such as beef (Snider and Baldwin, 1981;Schlichtherle-Cerny and Grosch, 1998;Cambero et al, 2000), lamb and pork (Macy et al, 1970), Vietnamese fish sauce (Park et al, 2002) and dried skipjack (Fuke and Konosu, 1991). In a previous study, we found that creatine and creatinine enhanced the characteristic flavor of thickness, mouthfulness and continuity when added to the Japanese noodle soup (Shah et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In fact, a correlation between the Cn/Cr ratio and the heat treatment was established in cooked ham samples concluding that this ratio could be used as a rapid and non-destructive indicator for the effectiveness of the heat treatment in cooked ham processes (Mora, Sentandreu & Toldrá, 2008a). Some authors reported the sensory properties of creatine and creatinine Snider & Baldwin, 1981), recommending the addition of creatine to broth because of the contribution of this compound to the full flavour of meat extracts (Schlichtherle-Cerny & Grosch, 1998).…”
Section: Introductionmentioning
confidence: 99%